Peptide nanosponges designed for rapid uptake by leukocytes and neural stem cells. Issue 29 (30th April 2018) - Yapa, Asanka S.; Wang, Hongwang; Wendel, Sebastian O.; Shrestha, Tej. B.; Kariyawasam, Nilusha L.; Kalubowilage, Madumali; Perera, Ayomi S.; Pyle, Marla; Basel, Matthew T.; Malalasekera, Aruni P.; Manawadu, Harshi; Yu, Jing; et al.
Abstract : Nanosponges for drug delivery. Abstract : The structure of novel binary nanosponges consisting of (cholesterol-(K/D) n DEVDGC)3 -trimaleimide units possessing a trigonal maleimide linker, to which either lysine (K)20 or aspartic acid (D)20 are tethered, has been elucidated by means of TEM. A high degree of agreement between these findings and structure predictions through explicit solvent and then coarse-grained molecular dynamics (MD) simulations has been found. Based on the nanosponges' structure and dynamics, caspase-6 mediated release of the model drug 5(6)-carboxyfluorescein has been demonstrated. Furthermore, the binary (DK20) nanosponges have been found to be virtually non-toxic in cultures of neural progenitor cells. It is of a special importance for the future development of cell-based therapies that DK20 nanosponges were taken up efficiently by leucocytes (WBC) in peripheral blood within 3 h of exposure. The percentage of live cells among the WBC was not significantly decreased by the DK20 nanosponges. In contrast to stem cell or leucocyte cell cultures, which have to be matched to the patient, autologous cells are optimal for cell-mediated therapy. Therefore, the nanosponges hold great promise for effective cell-based tumor targeting.